Self-face recognition in attended and unattended conditions: an event-related brain potential study. - Sui, J; Zhu, Y; Han, S (2006)
This study investigated whether neural mechanisms of self-face recognition are modulated by attention by recording event-related brain potentials associated with self-face recognition. Participants identified head orientations of self-faces and familiar or unfamiliar other faces presented briefly at the center of the visual field. Event-related brain potentials to self-faces and other faces were recorded when self-faces and familiar or unfamiliar other faces were either task relevant (attended) or irrelevant (unattended) in separate blocks of trials. We found that early face-specific event-related brain potential components such as the N170 and vertex positive potential did not differ between self-faces and other faces. Relative to familiar faces, however, self-faces induced an increased positivity over the frontocentral area at 220-700 ms. The increased positivity to self-faces relative to familiar faces between 500 and 700 ms was reduced in the attended relative to the unattended conditions, which arose from the fact that the amplitude to familiar faces during this time window was increased in the attended relative to the unattended conditions, whereas the event-related brain potential amplitude to self-faces was not influenced by attention. The event-related brain potential results suggest an automatic process of self-face recognition in human brains that occurs after face structure encoding and is independent of task relevance.